A Sentence Repetition Task for Catalan-Speaking Typically-Developing Children and Children with Specific Language Impairment - Gavarró, Anna (Frontiers in Psychology, 2017)
It is common to find that so-called minority languages enjoy fewer (if any) diagnostic tools than the so-called majority languages. This has repercussions for the detection and proper assessment of children with Specific Language Impairment (SLI) brought up in these languages. With a view to remedy this situation for Catalan, I developed a sentence repetition task to assess grammatical maturity in school-age children; in current practice, Catalan-speaking children are assessed with tests translated from Spanish, with disregard of the fact that the markers of SLI may differ substantially from one language to another, even between closely related languages. The test proposed here is inspired by SASIT [School-Age Sentence Imitation Test – English], designed for English by Marinis et al. (2011); some of the constructions targeted are challenging in a subset of languages, but not others, and are included because they are indeed affected in Catalan SLI; other constructions appear to be disrupted universally. The test involves canonical SVO sentences, sentences with third person accusative clitics (known to be problematic in Catalan SLI, but not in Spanish), passives, wh- interrogatives, subordinate clauses, subject and object relatives and conditionals. The test was administered to thirty typically developing 6- and 7-year-olds (as reported in Gavarró et al. 2012), and five children diagnosed with SLI (mean age 10;7). The results of the task were scored under two systems: (i) identical vs. non-identical repetition and (ii) identical, grammatical and ungrammatical repetition, with detail regarding the error type. The results for typically developing and SLI children showed differences between the groups: identical repetition was found in 88.9% of cases for typically developing children but only 48% for SLI children. Ungrammatical productions were higher for the SLI group, and so were grammatical but different repetitions, a trend which was found in every child individually. The results are compared to those available in the literature for similar languages and I discuss the impact of grammatical variation in language performance, in both typical and impaired development.